KUALITAS VISUM ET REPERTUM PERLUKAAN DI RUMAH SAKIT UMUM DAERAH MANDAU PERIODE 1 JUNI 2011– 30 JUNI 2013 - Jefryanto "; Dedi Afandi; Riswandi " (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTVisum et Repertum has a function in a process of proving the criminalcase to the health and human psyche. Visum et Repertum (VeR) of injury is thetype of VeR that most often requested by the investigator to a doctor who works inan emergency room. This research were done to find out the quality of VeR ofinjury in Mandau General Hospital during 1st June 2011-30th June 2013. Adescriptive retrospective research was designed using Herkutanto’s scoringmethod. All VeR data in Mandau General Hospital during 1st June 2011-30thJune 2013 were counted as samples a hundred fifty eight VeR data in MandauGeneral Hospital during 1st June 2011-30thJune 2013 were found injury survivorsmost cases are in the age group 22-40 years old as many as 94 victims (59,5%),mostly male 99 (62,7%). The most frequent violence that were experienced by thevictims were blunt violence was 150 VeR (94,9%). The preliminary unit of VeRabout 84,6% showed good quality, the reporting unit about 59% showed mediumquality and also the inference unit about 79,8% showed good quality. It can beconcluded that quality of VeR reports in Mandau General Hospital during 1stJune 2011-30th June 2013 was 72,64% which means medium quality.Keywords: Visum et Repertum, injury, the quality of Visum et Repertum of injury